Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jcm10194306
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome in Systemic Lupus Erythematosus; Knowledge from Population-Based Cohorts

Abstract: Background: Accurate knowledge of outcomes in Systemic Lupus Erythematosus (SLE) is crucial to understanding the true burden of the disease. The main objective of this systematic review was to gather all population-based studies on mortality, end-stage renal disease (ESRD) and cancer in SLE. Method: We performed a systematic literature search in two electronic databases (MEDLINE and Embase) to identify all population-based articles on SLE and survival, mortality, ESRD and cancer. The SLE diagnosis had to be ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…4 The incidence, prevalence, survival and mortality of SLE have been found to vary not only between countries but also within them. [5][6][7] Similar disparities were also observed in population groups of the same ethnicity living in different parts of the world, suggesting not only a genetic predisposition but also the influence of geographical and environmental factors. 8 Despite the heterogeneous nature of SLE, the broad spectrum of presentation and the severity of disease, these outcomes may be related to differences in ethnicity, economic status, educational level, well-being status, level of social support, geographical location and treatment adherence.…”
Section: Introductionsupporting
confidence: 59%
“…4 The incidence, prevalence, survival and mortality of SLE have been found to vary not only between countries but also within them. [5][6][7] Similar disparities were also observed in population groups of the same ethnicity living in different parts of the world, suggesting not only a genetic predisposition but also the influence of geographical and environmental factors. 8 Despite the heterogeneous nature of SLE, the broad spectrum of presentation and the severity of disease, these outcomes may be related to differences in ethnicity, economic status, educational level, well-being status, level of social support, geographical location and treatment adherence.…”
Section: Introductionsupporting
confidence: 59%
“…In a systematic literature review, Reppe Moe et al compiled data on mortality, endstage kidney disease (ESKD), and cancer from population-based studies, and found that cardiovascular disease was the most frequent cause of death over 15 years of followup. Moreover, 5-11% of patients developed ESKD, and no evidence for increased cancer incidence was found [22].…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…1 In the absence of diagnostic criteria, the "gold standard" case definition for SLE is "diagnosis confirmed by expert clinical assessment." 3,4 Individual case ascertainment (by experts) is therefore the gold standard case definition for all types of SLE research, including studies of SLE epidemiology at population level. Accordingly, to establish population-based SLE cohorts, three sequential steps appear necessary.…”
Section: Introductionmentioning
confidence: 99%